Infectious diseases: textbook - Ющук, Н. Д. инфекционные болезни 19401222-20231017 Николай Дмитриевич; Венгеров, Ю. Я. инфекционные болезни Юрий Яковлевич (GEOTAR-Media Publishing Group, 2020)
This edition of the textbook is signifi cantly updated and revised following the changes in the structure of incidence of different nosological entities of infectious diseases and their economic signifi cance, with new achievements in infectology and changes in educational program. The textbook is intended for the students of general and preventive medicine faculties. It can also be used for studying tropical medicine and post-graduate training of the doctors in the specialty "Infectious diseases".